PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP BARANG YANG TIDAK SESUAI PADA APLIKASI JUAL BELI ONLINE (FACEBOOK) DITINJAU DARI UNDANG-UNDANG RI NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN DI KOTA SUKABUMI - Siti Syarah Nuraisyah; Asti Sri Mulyanti (INTELIGENSIA MEDIA, 2024)
This research aims to find out the legal protection for consumers in transactions using Facebook media based on Law Number 8 of 1999 concerning Consumer Protection and to find out the legal remedies that consumers can do when they suffer losses due to transactions made through Facebook media. The method used in this research is a qualitative method. The type of research used by the author is normative juridical research. The type of research used by the author is descriptive research. As a normative legal research, the approach used is the statutory approach. The data collection technique in this research is literature study. The results showed that the legal protection of consumers in Facebook online transactions based on Law Number 8 1999 concerning consumer protection is as in Article 4 of the Law on Consumer Protection which states that consumers are entitled to compensation or replacement if the goods or services received are not in accordance with the agreement or not as they should be. Then the results showed that the legal efforts that consumers can make if they experience losses due to buying and selling goods online on social media Facebook consumers can report the incident to the Facebook platform itself, although Facebook does not directly handle reporting disputes can help prevent similar events in the future. If consumers are harmed by a large amount, consumers can get legal assistance from the Non-Governmental Consumer Protection Agency (LPKSM) and can also report to the Consumer Dispute Resolution Agency (BPSK) to process dispute resolution using conciliation mediation and arbitration.